If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 13 = -29 + -2x Reorder the terms: 13 + 5x = -29 + -2x Solving 13 + 5x = -29 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 13 + 5x + 2x = -29 + -2x + 2x Combine like terms: 5x + 2x = 7x 13 + 7x = -29 + -2x + 2x Combine like terms: -2x + 2x = 0 13 + 7x = -29 + 0 13 + 7x = -29 Add '-13' to each side of the equation. 13 + -13 + 7x = -29 + -13 Combine like terms: 13 + -13 = 0 0 + 7x = -29 + -13 7x = -29 + -13 Combine like terms: -29 + -13 = -42 7x = -42 Divide each side by '7'. x = -6 Simplifying x = -6
| 120=20*3.14/180*x | | 5d+4=13d | | (2r/3s)(9s/4r2)= | | q=5p-4 | | x+(x*0.18)=10000 | | (6x-2)(x+3)(5x+8)=0 | | (3m^3-(1/2)y)(3m^3-(1/2)y) | | -4g(3-2g)= | | 5(4x-1)-(2x+2)=x+5 | | 6(2)=2(3)+3x | | C=3n+4 | | (G-11)(G-8)=35 | | 2x-6y=-5 | | 3x-33=0 | | -4(2t+5)= | | (6x-2)(x+3)(5x+8)= | | (2/4*8) | | 3x-4=10x-55 | | 5t(7-t)-4(2t+5)= | | 4x^6-2x^73=9 | | 3x^3=1536 | | 5t(7-t)= | | n+5.1*2=14.6 | | 6p=8+2p | | 400y^2-9= | | 2d+5=6d-15 | | 4m=95 | | 3p+3=7p-5 | | (3a)^3*4a^4/(2a^2)^3*a^(-3) | | 5(2x-5)-5=10x-30 | | -8x^2+6x+35=0 | | 9x+8=3x+23 |